Metabolism of Human Diseases - Lammert, Eckhard; Zeeb, Martin (Springer, 2014)
The scientifi c community has increasingly recognized metabolic alterations as being critical components or even drivers of human disease. Metabolism of Human Diseases discusses the metabolism and signaling pathways in tissues and organs known to be relevant for common human diseases. It thus bridges the existing gap between biochemistry and physiology textbooks, on the one hand, and pathology textbooks, on the other hand. Metabolism of Human Diseases is directed at advanced students, doctors, and scientists from all categories of life sciences and medicine (e.g., biochemists, biologists, physiologists, pharmacologists, pharmacists, toxicologists, and physicians) with an interest in the metabolism and molecular mechanisms of human diseases, irrespective of their specialization.
Organ Physiology and Pathophysiology